Invasive African boneseed and a native shrub support similar faunal assemblages in a heavily infested landscape. (16th January 2023) - Carlos, Emma H.; Weston, Michael A.; Gibson, Maria; Rendall, Anthony R.
Abstract: Invasive weeds may provide habitat for wildlife in altered landscapes. We compare fauna within three types of sites in You Yangs Regional Park in central Victoria, Australia, that is, sites with an invasive shrub understory (African boneseed, Chrysanthemoides monilifera subsp. monilifera (DC.) T. Norl.), native shrub understory (snowy mintbush Prostanthera nivea ), and sites without an understory (open sites). Sites with an understory dominated by boneseed provided habitat for avian species and an introduced small mammal, comparable with sites with mintbush as the understory. Species‐specific models of common species suggest vegetation structure, rather than composition, drove this effect. Open sites differed in terms of avifaunal assemblage, and the abundance of three common native birds and one common invasive small mammal. Boneseed additionally showed phenological differences in fruiting and flowering and differences in flowering abundance when compared with mintbush, comparably offering resources to wildlife. Transitioning vegetation communities to more natural states should consider wildlife already depending on weeds, a dependency likely driven by a paucity of alternative native vegetation.